Bioactivities of Water Extract and Essential Oil from the Mace of Myristica fragrans Houtt - Widodo Santoso, Adit; Simamora, Adelina; Simamora, Adelina; Herawan Timotius, Kris; Herawan Timotius, Kris (Lembaga Penelitian Universitas YARSI, 2018)
Myristica fragrans Houtt (nutmeg) is used as a spice and flavour for food and beverages. It has been traditionally used to treat a number of medical conditions, including diabetes mellitus. The study was undertaken to scientifically validate the traditional use of mace from M. Fragrans. The objectives of this study were to evaluate α-glucosidase inhibition, antioxidant and antibacterial activities of water extract (WE) and essential oil (EO) from M. fragrans mace. Both WE and EO were evaluated for their α-glucosidase inhibitory activities in vitro and their antioxidant activities based on DPPH radical scavenging assay. Standard compounds were used for every test. Total phenolic and flavonoid contents of both extracts were also determined. The extracts were also tested for their antibacterial activities against six different bacteria by a well diffusion method. Both extracts showed inhibition activities against α-glucosidase, with WE showed stronger activity than EO (IC50 = 1.86 and 8.15 mg/ml). Good radical scavenging activities were observed for both extracts, with WE showed stronger activity than EO (IC50 = 1.51 and 4.59 mg/ml). WE showed higher content in phenolic than EO (47.84 and 37.21 mg GAE/100 g DW). Flavonoid content in WE was also higher than EO (215.36 and 30.12 mg RE/ml). Based on the well diffusion method, only EO exhibited antibacterial activities, with inhibition zone in the range 1.03 – 1.30 mm. The strongest activity was observed against Staphylococcus mutans. The results indicate WE and EO can be exploited further for pharmacological uses, in particular for their antidiabetic and antioxidant activities.